Fabrication of thermally conductive and electrically insulating polymer composites with isotropic thermal conductivity by constructing a three-dimensional interconnected network. Issue 23 (5th June 2019) - Yuan, Hao; Wang, Yang; Li, Ting; Wang, Yijie; Ma, Piming; Zhang, Hongji; Yang, Weijun; Chen, Mingqing; Dong, Weifu
Abstract : Efficient heat removal via thermal management materials has become one of the most critical challenges in the development of modern microelectronic devices. Abstract : Efficient heat removal via thermal management materials has become one of the most critical challenges in the development of modern microelectronic devices. However, the conventional polymer-based thermally conductive composites with randomly distributed filler particles usually yield an undesired value because of the lack of efficient heat transfer pathways. Therefore, constructing a three-dimensional interconnected filler structure is greatly desirable for realizing high thermal conductivity enhancement in composites. Herein, graphene oxide (GO) was used as a thermally conductive filler due to its excellent thermal conductivity and coated with polydopamine (PDA) to enhance its electric insulation performance. A unique "particle-constructing" method was adopted for fabricating highly ordered three-dimensional GO-based polymer composites, throughout which the GO-PDA formed an intact, uniform and well-defined network structure. The composite, even with a very low GO-PDA loading of 0.96 vol%, exhibited both high in-plane (4.13 W m −1 K −1 ) and through-plane (4.56 W m −1 K −1 ) thermal conductivities and also presented excellent electrically insulating properties (>10 14 Ω cm). These composites have promising applications in heat dissipation of next-generation portable and collapsible electronic devices.